PENGARUH PENGUNAAN JAHE MERAH SEBAGAI FEED ADDITIVE TERHADAP INCOME OVER FEED COST AYAM BROILER - Martin Umbu Duka (Jurnal Sains Peternakan, 2014)
The aim of this research was to know effect of using red ginger (Zingiber officnale rosc) as feed additive on income over feed cost of broiler management. One hundred of broiler DOC strain cp 707 were plotted into five different groups and each group was further divided into four sub-groups. Each group was given diffent ration i.e : P0 (control ration without red ginger added) : p1 ,p2,p3, and p4 (control ration added with red ginger at level 1%, 2%, 3%, 4% ) the broiler were raised  for 35 days variable of this research was income over feed cost ( IOFC ) the collected deta were subjected to analysis of completely randommiseg design (CRD) the result showed that broiler given ration with red ginger showed significantly effect on income over feed cost (p< 0.05) the highest IOFC was P0 11.278.Futher research have to be conducted to evaluate the potential of red ginger as a source of phytobiotic feed additive to replace the chemical antiobioties. Keyword: Red Ginger, IOFC, Broiler.